Ujian Nabi Ibrahim Menjadi Pemimpin - Zaiyadi, Ahmad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2018)
The exams of Allah to his servant, is a gift that contains virtue values. Abraham is a prophet, who had the virtue of being appointed as a leader for himself, his family and people. The leadership of the Abraham did not go through an instant process, in the Qur'an it was told how Abraham had been tested by God several times in the form of orders or prohibitions. Because of his obedience to God he was able to carry out all these commands perfectly, so that in the end God glorified himself as well as some of his descendants as leaders of the people. Jews, Christians and Islam including religion delivered by the descendants of the prophet Ibrahim. thus, God's examination of Abraham can be explored through verses about the examination of Allah to the Abraham.